2014
DOI: 10.17219/acem/37341
|View full text |Cite
|
Sign up to set email alerts
|

Serum and Urinary MIP-1α and IP-10 Levels in Children with Urinary Tract Infections

Abstract: Objectives. Urinary tract infection (UTI) is a common bacterial disease in infants and children, with potentially serious complications, including kidney damage. The aim of this study was to test whether serum and urinary levels of interleukin-6 (IL-6), macrophage inflammatory protein-1α (MIP-1α) and interferon-γ-inducible protein-10 (IP-10) can be used as biomarkers in children with urinary tract infections. Material and Methods. The study group consisted of 22 children with UTI and 20 controls. Blood and uri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…and Gorczyca et al . did not confirm a rapid decrease of the cytokine levels in children with UTI [35, 39]. In our patients, samples of urine were obtained in the first 48 hours from admission, and in some patients also after initiation of treatment.…”
Section: Discussionmentioning
confidence: 73%
“…and Gorczyca et al . did not confirm a rapid decrease of the cytokine levels in children with UTI [35, 39]. In our patients, samples of urine were obtained in the first 48 hours from admission, and in some patients also after initiation of treatment.…”
Section: Discussionmentioning
confidence: 73%
“…This study showed that leukocyturia without histological inflammation did not have elevated urine CXCL10 levels; however, there were few urine cultures reported to confirm or exclude infection at the time of biopsy. Other studies have reported association of CXCL10 with urinary tract infection risk in both transplant 32 and nontransplant 32,55,56 settings. In clinical use, caution will still be required to exclude urinary tract infection from the differential diagnosis, prior to proceeding with more invasive diagnostics.…”
Section: Discussionmentioning
confidence: 97%
“…UTI is defined as a significant bacteriuria growth of a single pathogen: At least 10 4 colony forming units (CFU) for catheter specimens and at least 10 5 CFU for midstream clean catch specimens) or 5x10 4 CFU and significant pyuria in a patient with fever or other clinical symptoms (5)(6)(7)(8)(9). Recurrent UTIs are defined as repeated infections with a different pathogen agent, while relapsing UTIs represent repeated infections with the same pathogen (5)(6)(7)10,11).…”
Section: Introductionmentioning
confidence: 99%